The Role of MicroRNA-206 in the Regulation of Diabetic Wound Healing via Hypoxia-Inducible Factor 1-Alpha - Zeming Bai; Dapeng Zhou; Kai Tao; Feng Lin; Hongyi Wang; Haiwei Sun; Ruidi Liu; Zhe Li (Biochemical Genetics, 2025)
Successful wound healing in diabetic patients is hindered by dysregulated miRNA expression. This study aimed to investigate the abnormal expression of miRNAs in diabetic wound healing and the potential therapeutic role of modulating the miR-206/HIF-1α pathway. MicroRNA assays were used to identify differentially expressed miRNAs in diabetic wound sites and adjacent areas. In vitro models and a rat diabetic model were established to evaluate the effects of miR-206 on HIF-1α regulation and wound healing. The study revealed differential expression of miR-206 in diabetic wound tissues, its interaction with HIF-1α, and the inhibitory effect of miR-206 on cell growth under high glucose conditions. Modulating the miR-206/HIF-1α pathway using miR-206 antagomir promoted HIF-1α, CD34, and VEGF expression, ultimately enhancing diabetic wound healing.

Backwater rise upstream of a stream-crossing culvert due to large wood accumulation and sediment deposition - Qiang Li; Ruihua Nie; Lu Wang; Ruidi Bai; Xingnian Liu; Chao Liu (Journal of Hydrology, 2025)

Reduce pollution, establish protected areas, manage fisheries properly? How to protect coral reefs based on carbon trading - Yuntao Bai; Ruidi Hu; Lan Wang; Delong Li (Frontiers in Marine Science, 2024)
As coral reefs around the world have suffered serious damage, it is necessary to protect them. Common modes of coral reef protection include reducing pollution, setting up reserves and managing fisheries rationally. In order to derive the applicable scope of various protection modes for coral reefs, this article constructs three differential game models and compares and analyzes the equilibrium results obtained by the models. Finally, the study shows that whether for developed or developing countries, when the benefits of coral reef treatment are small, the mode of reducing pollution can achieve the maximum benefit. As the benefits of coral reef treatment gradually increase, the mode of setting up nature reserves can achieve the maximum benefit. It is worth noting that the greater the carbon emission rights obtained by the number of coral reefs, the greater the benefits of coral reef treatment, the more likely developed countries will adopt the mode of setting up reserves.

Flow measurement by vegetated weirs: An investigation on discharge coefficient reduction by crest vegetation - Ruidi Bai; Maolin Zhou; Zhou Yan; Jianmin Zhang; Hang Wang (Journal of Hydrology, 2023)

Free-surface undulation and velocity turbulence in shallow undular hydraulic jumps - Hong Hu; Hang Wang; Dongzi Pan; Xiekang Wang; Ruidi Bai (Ocean Engineering, 2023)

A comparative study of pre-aeration effects on hydraulic jump air–water flow properties at high Froude numbers - Rongcai Tang; Ruidi Bai; Hang Wang (Environmental Fluid Mechanics, 2021)

Experimental investigation of bubbly flow and air entrainment discharge downstream of chute aerators - Ruidi Bai; Shanjun Liu; Zhong Tian; Wei Wang; Faxing Zhang (Environmental Fluid Mechanics, 2019)